Exploring the potential of Nyonya Kuih residues as the substrate for yeast cell protein production - Pei, Ling Tang; Wei, Herng Wong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Nyonya kuih, a popular Malaysian traditional cuisine that have short shelf life due to their high moisture and fat contents. The unsold kuihs usually ended up as food residue. Thus, kuih talam (KT) and kuih lapis (KL), two varieties of Nyonya kuih were chosen as the investigative substrates to explore the recycling potential of this food residue. Initially, the effect of fat content on the enzymatic hydrolysability of the residues to release fermentable sugar was investigated. The efficiency of lipase-pretreatment (LP), polyvinylpyrrolidone-post-treatment (PVP) and their combination in lipid removal was determined. Then, the potential of the resulting glucose-rich hydrolysates for Saccharomyces cerevisiae yeast cell biomass production was assessed, with molasses as the positive control. Results indicated that combined LP and PVP (LP-PVP) significantly (p<0.05) reduced crude fat content, while increasing the total sugar content of KT and KL hydrolysates by approximately 3.4 and 26.3 times, respectively. Yeast cell biomass produced from KT and KL hydrolysates were increased by 23% and 39%, respectively after LP-PVP treatment. Despite the yeast cells’ yield (by dry cell weight) from molasses fermentation being 19% and 11% higher than those from KT and KL hydrolysates, respectively, KT and KL hydrolysates were proven superior due to the significantly higher (p<0.05) crude protein content in yeast cell produced from both hydrolysates. Further study is needed to enhance yeast cell yield from the fermentation of KT and KL hydrolysates, thereby improving the overall protein yield from the fermentation process. This study provides new insight into a novel food residue recycle strategy, promoting sustainable food production aligned with SDG 12.